Assisting MSMEs in Utilizing Digital Marketing and Online Product Marketing Strategies in Jati Village, Tarogong District - Rahayu, Dinar; Nugraha, Yopi; Rosliani, Elin; Habil, Riski (Indonesian Journal of Community Empowerment (IJCE), 2023)
Digital marketing has become crucial for Micro, Small, and Medium Enterprises (MSMEs), especially when facing the challenges of the technological era. With technological advancements, the internet, and the digital revolution, MSMEs must be prepared to understand the use of social media to develop increasingly advanced technologies and meet the technological needs for small business development in the future. However, not all MSME operators in the Desa Jati community have yet been able to leverage technology to support their businesses. Addressing this issue, the aim and solution of this research is to provide Digital Marketing and Strategy assistance to these MSMEs. The program has shown significant positive impacts. Participants in the training have experienced improvements in their digital marketing knowledge and skills, as evidenced by their performance in evaluations.